1287. Seizing Opportunities for Intervention: Changing HIV Knowledge Among Men Who Have Sex With Men and Transgender Women Attending Trusted Community Centers in Nigeria. (26th November 2018) - Jones, Milissa; Omari, Habib; Adebajo, Sylvia; Gaydos, Charlotte; Kokogho, Afoke; Baral, Stefan; Nowak, Rebecca; Ake, Julie; Charurat, Manhattan; Robb, Merlin L; Crowell, Trevor A; ,
Abstract: Background: Knowledge of HIV risk factors and risk reduction strategies is essential for HIV prevention in key populations, including men who have sex with men (MSM) and transgender women (TGW). We described factors associated with HIV-related knowledge and evaluated the impact of counseling and care at trusted community health centers serving Nigerian MSM and TGW. Methods: The TRUST/RV368 cohort recruits MSM and TGW via respondent driven sampling in Abuja and Lagos, Nigeria. Participants undergo a structured interview with five knowledge-testing questions at enrollment and after 9 and 15 months. Routine HIV/STI screening, free condoms/lubricants, and counseling about safer sex practice is provided. Multivariable Poisson regression with generalized estimating equations was used to calculate risk ratios (RRs) and 95% confidence intervals (CIs) for factors associated with answering more knowledge questions correctly. Pearson's chi-squared test was used to compare the proportion of participants answering each question correctly at enrollment and subsequent visits. Results: From March 2013 to December 2017, 2, 090 biological males were enrolled with median age 23 [interquartile range 20–27] years, including 234 (11.2%) with female gender identity. Of 1691 participants with known HIV status, 836 (49.4%) were positive. The mean number of HIV knowledge questions correctly answered was 2.37, 2.98, and 3.09 at enrollment, 9, and 15 months, respectively. Participants demonstrated increased HIV knowledge after 9 (RR 1.15 [95% CI 1.03–1.28]) and 15 months (1.18 [1.05–1.32]). Factors associated with increased knowledge included HIV positivity (1.17 [1.11–1.23]), higher than senior secondary education when compared with less than senior secondary (1.24 [1.12–1.37]), and almost daily internet use when compared with never (1.17 [1.08–1.27]). Knowledge gains were driven primarily by improved understanding of condom and lubricant use (figure). Conclusion: While HIV knowledge improved during enrollment in the cohort, it remained suboptimal. Multiple modalities may be needed to fully inform Nigerian MSM and TGW of risk reduction strategies. Interventions that involve internet access to deliver educational materials may be a useful adjunct to direct counseling at healthcare centers. Disclosures: All authors: No reported disclosures.